2000
DOI: 10.1176/appi.ajp.157.2.172
|View full text |Cite
|
Sign up to set email alerts
|

Late-Onset Schizophrenia and Very-Late-Onset Schizophrenia-Like Psychosis: An International Consensus

Abstract: In terms of epidemiology, symptom profile, and identified pathophysiologies, the diagnoses of late-onset schizophrenia (illness onset after 40 years of age) and very-late-onset schizophrenia-like psychosis (onset after 60 years) have face validity and clinical utility. General adoption of these categories will foster systematic investigation of such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
400
5
51

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 592 publications
(475 citation statements)
references
References 99 publications
19
400
5
51
Order By: Relevance
“…Because numerous studies have shown that the onset of schizophrenia tends to be later in life in women than in men (Howard et al, 2000), and the present results indicate that the separation between women with schizophrenia and HC women might differ from that between men with schizophrenia and HC men at various ages, understanding the effects of aging in schizophrenia will likely require studying LTL (and other aging parameters) separately in men and women (Ramsey et al, 2013).…”
Section: Discussionmentioning
confidence: 76%
“…Because numerous studies have shown that the onset of schizophrenia tends to be later in life in women than in men (Howard et al, 2000), and the present results indicate that the separation between women with schizophrenia and HC women might differ from that between men with schizophrenia and HC men at various ages, understanding the effects of aging in schizophrenia will likely require studying LTL (and other aging parameters) separately in men and women (Ramsey et al, 2013).…”
Section: Discussionmentioning
confidence: 76%
“…Tomando por base o consenso internacional sobre esquizofrenia de início tardio (Howard et al, 2000), os diagnósticos mais plausíveis para os casos 1 e 2 são a esquizofrenia de início tardio (late-onset schizophrenia) e a psicose esquizofreniforme de início mais tardio (very late-onset schizophrenia-like psychoses), respectivamente.…”
Section: Discussionunclassified
“…Os dois casos clínicos evidenciam alguns fatores de risco citados na literatura a respeito dos diagnós-ticos citados, como a presença de isolamento social prévio (Henderson e Kay, 1997) e o sexo feminino (Almeida et al, 1995a;Barclay e Almeida, 2000;Brodaty et al, 1999;Holden, 1987;Howard et al, 2000;Silveira et al, 2004). No caso 2, podemos observar outro fator de risco para a patologia, o déficit auditivo (Almeida et al, 1995a).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…early-onset schizophrenia, EOS) je shizofrenija z začetkom v ali pred 40. letom starosti. Nekateri avtorji uporabljajo tudi starostno mejo 45 ali 50 let (1,(4)(5)(6)(7). Pozno nastala shizofrenija (angl.…”
Section: Definicijeunclassified